Nicholas Roosevelt in A Front Row Seat: Hungary in the 1930s As Reflected in the Memoirs of an American Diplomat - Mathey, Éva (Acta Neerlandica, 2020)
As Nicholas Roosevelt put it in the foreword of his memoirs a “combination of circumstances gave [him] the front row seat at numerous important […] events in Europe during the interwar period,” which made it possible for him to “study history in the making” both as a journalist working for acknowledged dailies of the time, such as The New York Times and The New York Herald Tribune, and as a diplomat who served at various European posts in Europe including Hungary between 1930 and 1933. Due to both of these positions Hungarians considered Roosevelt a highly influential person, who could possibly air and expose Hungary’s situation in the international community after World War I, and help further the revision of the Treaty of Trianon. Drawing on his memoirs, diplomatic exchanges, as well as a selection of his newspaper and magazine articles, the essay proposes to reflect on how Roosevelt viewed Hungary, and whether his various forms of written narratives could have any effect and exert any influence in this regard.